Pengaruh Kegiatan Musyawarah Terhadap Sosialisasi Penanggulangan Sampah di Pasar Cisaat Kabupaten Sukabumi - Rima Nurani Sukma; Abdullah Asruri (STISIP Widyapuri Mandiri Sukabumi, 2022)
This study aims to determine the deliberation activities that can provide information on waste management at Cisaat Market, Kabupaten Sakabumi, market residents' deliberation activities that can instill confidence in the socialization of waste management, and to determine the trust of market residents in raising awareness of market cleanliness. The population is 865 people as market residents or traders. The sample selected was 87 people with the Probability Sampling sampling technique. The research method is quantitative to show the relationship between variables as well as reflect the type and number of problem formulations. There are two variables, namely the independent variable (x) = Community Deliberation Activities and the dependent variable (y) = Use of Socialization Media for Waste Management. While the data collection techniques through literature study, observation, interviews, and questionnaires. The results of the analysis of the description of the market residents' deliberation as an independent variable can be obtained by good criteria. This is based on the total score obtained from 87 respondents regarding the level of condition (how good) of the market citizen consultation variable (Vx) which is 3708. This figure is in good criteria. The results of the analysis of the description of the use of waste management socialization media at Cisaat Market, Sukabumi Regency based on the data on the number of scores obtained from 87 respondents about the level of condition (how good) of the variable using the waste management socialization media (Vy) which is 3834. This figure is in good criteria . The influence of market residents' deliberation on the use of socialization media for handling waste has a positive effect with the correlation coefficient number found to be 0.363 after being compared with the interpretation table of the correlation coefficient, namely the r count ranges from 0.20-0.399 so that it is categorized as low. After being calculated with the coefficient of determination formula, the contribution is 13.18%, while the remaining 86.82% is another factor that is not removed. Furthermore, the results of the significance test of the moment product correlation were found to have a relationship, and it applies to all respondents. This means that there is sufficient evidence to state that there is an influence of market residents' deliberation on the use of socialization media for handling waste at Cisaat Market, Sukabumi Regency, so that the hypothesis is accepted.